A History of Opium Commodity Chains in Mexico, 1900–1950. Issue 2 (2nd December 2022) - Fernández Velázquez, Juan; Smith, Benjamin
Classic treatments of both the opium industry and the international drug trade tend to leave out Mexico's opium production. Yet the industry, which emerged in the 1920s, both fulfilled U.S. demands and shaped the Mexican narcotics trade.